Stability of the Dispersed Band in a Shallow Layer Settler - Margarida Ribeiro (2008)
The present study is aimed at shallow-layer settlers, involving pilot plant data collecting about the thickness of the dispersion band at different points along its length and its use in simulation work. At steady state, after step inputs in the agitation power, the length of the dispersed band varied in time, and didnt return to its initial condition. Although clean, pure fluids were used, crud formation was observed and acquired relevance especially for long period experiments. This behavior brought out the fact that crud formed during the experimentation disturbed the stability of the dispersed band. Crud analysis, performed by fluorescence microscopy, suggested the presence of bacteria. This bacterial nature of the crud was confirmed and biocide utilization seemed to be adequate for its minimization.